Cerita Rakyat Ondorante Pembentuk Pola Perilaku dan Identitas Masyarakat - Retno M, Laura Andri (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Folklore has a position and a really important function for its proponent people. One of those folklores that exist in Pati, Central Java, is a folklore called Ondorante. In addition to completely describe the story, this research also intend to discover the transmission process and the funtions that appear in the Ondorante. Finally, through qualitative descriptive approach by interview, observation and bibliographical techniques, it appears that the folklore doesn’t only play its role as an entertainment, education, reflection or ritual, but also offers a consciousness to the people about the past, about who were their ancestors and the origin of how their native land formed.